Experimental Demonstration of Platoon Formation Using a Cooperative Merging Controller - Wouter Scholte; Tom van der Sande; Peter Zegelaar; Henk Nijmeijer (IEEE Open Journal of Intelligent Transportation Systems)
Road safety and traffic congestion are amongst the main challenges in current transportation systems. Literature shows that these challenges can be tackled using cooperative platoons, which is a technique in which vehicles use communication to drive closely behind each other in a string. An important topic of research regarding cooperative platoons is merging vehicles into a platoon at highway on-ramps. In previous work, the authors proposed a control strategy for the merging of a single cooperative automated vehicle into a platoon of vehicles at highway on-ramps. In this paper, the performance of this controller is demonstrated using experiments with two full-scale vehicles. During these experiments a two-vehicle platoon is formed in a limited distance. Several scenarios with different trajectories of the preceding vehicle are investigated. The preceding vehicle can be accelerating or decelerating simulating disturbances encountered in a larger platoon. In all experiments, the maneuver is successfully executed. The results of these experiments show the large potential of the proposed merging controller.